P3.218 Increasing Trend of HIV/AIDS Among Arab and Jewish Males in Israel, 1986–2010. (13th July 2013) - Mor, Z; Grayeb, E; Beany, A; Grotto, I
Abstract : Background: HIV/AIDS-burden in Israel is low (∼6 cases:100, 000 population), while sub-populations characterised by high-risk behaviours are affected disproportionally. This study aims to compare HIV/AIDS-burden in males between Israeli Jews and Arabs, which are the biggest monitory in Israel. Methods: The National HIV/AIDS Registry (NHAR) was the source for HIV/AIDS-infection records, while the Israeli Central Bureau of Statistics was used to determine groups-specific disease rates. Results: Between 1986 and 2010, 3, 499 HIV/AIDS-infected males were reported: 3, 369 (96.3%) Jews and 130 (3.7%) Arabs, in an average annual incidence of 5.5 and 0.8 per 100, 000 populations, respectively, p = 0.05. Of all Jews, 1, 018 (29.9%) were born in Ethiopia, while 2, 389 were Jews who were not Ethiopian-born (JNE). Most Arabs (N = 99, 74.8%) were Muslims, followed by 21 (16.2%) Christians and 13 (10%) Druze. AIDS rather than HIV upon reporting was diagnosed in 568 (23.8%) of JNE and 31 (23.8%) of the Arabs, p = 1. The most affected age-group among JNE was 25–34 and in Arabs 20–24, and the respective cumulative death rates were 24.9% (N = 594) and 32.5% (N = 40), p = 0.1. The point-prevalence in 2010 was 58.4 and 11.4 per 100, 000 for JNE and Arabs, and in adults aged 15–49, was 98.0 and 20.4 per 100, 000, respectively. In Muslims, Christians and Druze, the point-prevalence was 4.2, 11.2 and 7.1 per 100, 000; and in adults aged 15–49 was 20.4, 52.6 and 21.6, respectively. The most common risk-groups among JNE was MSM (N = 1, 223, 51.2%), followed by IVDU (N = 661, 27.7%); while among Arabs was MSM (N = 63, 48.1%), followed by heterosexuals (N = 36, 27.3%). Conclusions: HIV/AIDS-burden in Arab males was significantly lower than in Jews. Among Arab-males, HIV/AIDS-burden was highest in Christians than in Druze and Muslims. The proportion of MSM of all males, regardless of their religion is increasing. Interventions aiming to prevent further HIV-transmission should address cultural, linguistic and behavioural characteristics.